Analisis Perbandingan GCG Pada Kinerja Keuangan Perbankan Syariah Dengan Perbankan Konvensional - Revina Anyndita; Putri Salsadila; Mohamad Djasuli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The implementation of Good Corporate Governance in banking is expected to affect banking performance, because the implementation of Good Corporate Governance can improve financial performance. After the issuance of the Indonesian Banking Regulation (PBI) Number 8/4/PBI/2006 which was later amended by Bank Indonesia Regulation Number 8/14/PBI/2006, it became clear how good and correct Good Corporate Governance practices are. All banking companies are competing to improve corporate image through their respective Good Corporate Governance Reports. It is certain that there are differences between the implementation of Good Corporate Governance between conventional banking and Islamic banking. Because seen from the banking goals are definitely different. The purpose of this study is to see whether there is a difference between the implementation of Good Corporate Governance in conventional banks and Islamic banking. And the result is that the implementation of Good Corporate Governance in the banking industry is actually the same, both conventional banks and Islamic banks because it has been regulated by Bank Indonesia. The implementation of Good Corporate Governance begins with a vision and mission of the company which is then adjusted to the applicable laws and regulations. Then there is an additional organizational structure for Islamic banks in the implementation of Good Corporate Governance with the formation of the Sharia Supervisory Board and the National Sharia Council. Both of them serve as special supervisors of Islamic banks. Apart from that, the difference lies in the corporate culture.